THE EFFECT OF TWO DIMENSION MOTION PICTURE ON STUDENTS’ VOCABULARY MASTERY - Milah Milah; M. Zaini Miftah; Zaitun Qamariah (IKIP Siliwangi, 2022)
This study was aimed to measure that students who are taught using two-dimensional motion picture provide a higher vocabulary mastery or not in seventh grade at SMPN 4 Satu Atap Murung. Quasi-experimental design was used in this research. Quasi-experimental aims to assess cause and effect between research objects. The instrument used is a test. The question is in the form of multiple choice, there are 50 items of vocabulary variety. Researchers designed lesson plans, administered treatment and calculated student scores through pre-test and post-test. The population in this study were 168 students of SMPN 4 Satu Atap Murung. While the sample in this study were 50 seventh grade students of SMPN 4 Satu Atap Murung. Data analysis used SPSS 24 software. Based on the results of the analysis, the two-tailed t-test significance was lower than alpha 0.05 or 0.001 < 0.05. Based on manual calculations, the results obtained that the value obtained is higher than the ttable value at a significance level of 5% or 3.5 > 2.01. Can say that teaching by using two dimension motion picture gives students higher English vocabulary. Keywords: Effect, Two Dimension Motion Picture, Vocabulary Mastery